Capturing depressive symptoms in Filipino college students : a preliminary phase to scale construction - E. Porillo, Jo-ann; R. Tungol, Joy (Penerbit Universiti Kebangsaan Malaysia, 2021)
The major intent of this study is to identify and describe various symptoms associated with major depressive disorder (MDD) among Filipino college students. Data gathered from semi-structured interviews with experts and student participants who are identified as depressed using the Patient Health Questionnaire-9 (PHQ-9) as a screening tool were transcribed and coded. Surveys with open-ended questions are also employed for student participants to comprehensively capture their experiences. The triangulation process used in this qualitative research is described. Data were examined and clustered according to the similarities, differences, and relationships of categories via a repertory grid. Through a constant comparative approach, the findings of this study revealed that the most common depressive symptoms among Filipino college students are categorized into themes and subthemes, namely: (1) Affective symptoms (emotional vulnerability and flat affect) (2) Mental codes (cognitive issues and thought of death and selfharm), and (3) Behavioral Change (isolation, disguised emotional expression, crying spell, and physical disturbances). Themes may be utilized as factors for developing a depression scale designed for Filipino college students. Policies and interventions are needed to support college students who are at risk of depression.